The impact of COVID-19 on athletes` training, mental health and performance preparedness - perspective of a national shooter and orthopaedic resident - Mastura Rahim, S.; Lie, D. T. T. (TJTO&C - The Transient Journal of Trauma, Orthopaedics and the Coronavirus, 2020)
The COVID-19 pandemic came unannounced and affected many countries, infecting millions and resulting in thousands of lives lost. Unprecedented efforts have been taken globally to control the spread of this virus. Most sectors in the economy have been disrupted with most effort and resources directed to the healthcare industry. Workers who are in `non-essential` industries are required to work from home. Singapore was hit early and was in the centre of global media attention in February.